TOGAF ADM Framework Design at Private Insurance Company PT Tugu Pratama - Anindita, Tiara; Huda, Muhammad Qomarul (oneamrd (One a Mllions Dreams Corporation), 2025)
This study aims to design an Enterprise Architecture (AE) using the TOGAF ADM (Architecture Development Method) framework for insurance companies, with a focus on improving operational efficiency, regulatory compliance, and customer experience. TOGAF ADM was chosen because of its ability to provide a structured and comprehensive approach to developing an architecture that is aligned with business objectives and technology needs. This research method involves analyzing business needs, mapping key business processes such as claim submission, insurance registration, promotion, customer service, and identifying supporting technologies such as HRD, finance and IT services. The results of the study indicate that the implementation of TOGAF ADM can help insurance companies integrate systems, improve data security, and ensure compliance with industry regulations. In addition, this design also supports product and service innovation, and increases the scalability and flexibility of the architecture to face market dynamics. However, this study also identified several limitations, including implementation complexity, significant resource requirements, and challenges in integrating legacy systems. Overall, the TOGAF ADM AE design offers a strong framework for the digital transformation of insurance companies, with the potential for positive impacts on operational efficiency, customer satisfaction, and business competitiveness.